AB0200 Factors associated with functional capacity in a brazilian cohort of patients with rheumatoid arthritis: results from the '' real '' study. (12th June 2018) - Pugliesi, A.A.V.; Macedo, E.D.A.; Bertolo, M.B.; Giorgi, R.; Radominski, S.; Pereira, I.; Guimaraes, M.F.; Louzada, P.; Cunha, M.D.F.; Bonfiglioli, K.; Brenol, C.; Mota, L.M.H.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is associated with impairments in functionality, affecting aspects such as physical capacity, independence, mental health, social and professional life. Health Assessment Questionnaire-Disability Index (HAQ-DI) is a validated tool for assessing functional capacity in RA patients. A simple questionnaire with a score of 0 to 3 is applied, with an inverse relationship between grade and functionality. Previous studies have shown worse functional indexes in patients with high disease activity and established joint damage. Objectives: To relate clinical, laboratory and therapeutic aspects with HAQ-DI in a large cohort of Brazilian patients. Methods: A prospective, multicenter cohort study ("REAL" Study) involving 11 Brazilian centres specialised in the treatment of RA patients. All patients were submitted to at least 3 clinical evaluations in a 12 month period. Only patients older than 18 years and classified as RA according to 1987 (ACR) or 2010 (ACR/EULAR) criteria were evaluated. HAQ-DI was applied for assessing functional capacity, and the results were analysed for association with clinical, laboratory and therapeutic elements. Comparison between groups was performed using Mann-Whitney or Kruskal-Wallis tests. Results: Overall, 1116 patients (89.43% females, mean age 58±11 years) took part in the study. Rheumatoid factor (RF) in high levels and bone erosion were both associated with higher HAQ-DI indexes (p: 0.0244 and p<0.0001, respectively). Of all patients, 89.7% were using conventional synthetic disease-modifying antirheumatic drugs (DMARDs) and 36.5% were on biologic DMARDs or targeted-synthetic DMARDs. The use of any conventional synthetic DMARD was associated with lower HAQ-DI indices (p: 0.0243), while the use of any biologic DMARD or targeted-synthetic DMARD was related to greater functional impairment (p: 0.0018). By evaluating separately, abatacept (p: 0.0046), rituximab (p: 0.0001) and tocilizumab (p: 0.0441) were associated with higher levels of HAQ-DI. The results are summarised in table 1. Conclusions: In our prospective cohort, patients with high levels of RF, bone erosion, in use of any biologic DMARD or targeted-synthetic DMARD, abatacept, rituximab or tocilizumab had worse functional capacity indexes. When compared to non-use, the use of any conventional DMARD was associated with better rates of HAQ-DI. References: [1] Drossaers-Bakker KW, de Buck M, van Zeben D, et al. Long-term course and outcome of functional capacity in rheumatoid arthritis: The effect of disease activity and radiologic damage over time. Arthritis Rheum1999;42:1854. [2] Scott DL, Pugner K, Kaarela K, et al. The links between joint damage and disability in rheumatoid arthritis. Rheumatology (Oxford)2000;39:122. Disclosure of Interest: None declared